2018
DOI: 10.1177/0886260518754473
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Study of Christian Church Support for Domestic Violence Victims: 2005-2015

Abstract: The results of this study indicated that change is slow. Members want their clergy to become more educated in counseling and in speaking about domestic violence from the pulpit. Clergy felt comfortable in making referrals for professional counseling, while the majority of members would prefer counseling with their pastor if they were in a violent relationship. Both clergy and members want to create a safe and supportive environment for victims/survivors of violent relationships. Findings from this study exempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Faith-based organizations have been credited as providing critical support to those in family violence situations (de la Rosa, Barnett-Queen, Messick, & Gurrola 2016;Zust, Flicek, Moses, Schubert, & Timmerman 2018). Churches and other faith-based institutions provide informal counselling and support as well as community assistance necessary to keep them safe (Fuchsel 2012).…”
Section: Why Family Violence Increases After Disastersmentioning
confidence: 99%
“…Faith-based organizations have been credited as providing critical support to those in family violence situations (de la Rosa, Barnett-Queen, Messick, & Gurrola 2016;Zust, Flicek, Moses, Schubert, & Timmerman 2018). Churches and other faith-based institutions provide informal counselling and support as well as community assistance necessary to keep them safe (Fuchsel 2012).…”
Section: Why Family Violence Increases After Disastersmentioning
confidence: 99%
“…Collaboration between community service agencies and faith-based organizations has also demonstrated positive impacts in reducing family violence (Johnson, 2015;Wang, Horne, Levitt, & Klesges, 2009). Conversely, other studies have shown that the relationship between faith and violence can be paradoxical, offering both solutions to and, in some cases, exacerbating violence (Petersen, 2016;Zust et al, 2018). Although faith-based organizations are a source of emotional comfort and practical support, they may also perpetuate silence.…”
mentioning
confidence: 99%
“…Despite the paucity of research on the impact of faithbased responses to Tongan and Pacific family violence, the international literature highlights the importance of such initiatives for faith-based communities. Previous research has demonstrated both positive and negative results from faith-based interventions (Aten, McMinn, & Worthington Jr, 2011;Kaybryn & Nidadavolu, 2012;Le Roux, 2015;Zust, Flicek, Moses, Schubert, & Timmerman, 2018). Previous studies show that increased participation in faith-based communities not only provides strength, resilience, healing, and wholeness, but also can protect against and prevent the incidence of family violence (Ellison et al, 2007;Nason-Clark, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Christian faith can also function as a barrier for seeking help. Some victims would rather endure violence to keep the family together than be seen to be compromising their faith by leaving a violent relationship, and as such attracting shame and stigma (Ringel & Bina, 2007; Ting & Panchanadeswaran, 2016; Zust et al, 2018). Alternatively, Christian faith can play a key role in addressing domestic violence and holding perpetrators to account (Ellison et al, 2007; Johnson, 2015).…”
mentioning
confidence: 99%